Presenting identification keys and future study on seagrass Halophila major in Indonesia - Robba Fahrisy Darus; Dietriech Geoffrey Bengen; Neviaty Putri Zamani; Meutia Samira Ismet (Depik Jurnal)
Halophila major is a new species with a wide distribution across various regions in Indonesia. The species was identified in 2020 through a combination of morphology and molecular approaches. Several studies have shown that it has a similar morphology to H. ovalis, which causes significant confusion during identification. Therefore, this study aims to describe the key identification and habitat of H. major and summarize seagrasses study opportunities based on the trend of published articles. A bibliometric analysis was used to summarize the habitat, morphometrics, molecular confirmation, and trend of seagrass topics in Indonesia. Based on the scientific articles, H. major has bigger morphometrics than H. ovalis. In addition, the number of paired and branching cross veins was reported to be an identification key of H. major. The species was also considered a deep ovalis found in 2-4 m depth. Genetically, the Internal Transcribed Spacer (ITS) gene marker was appropriate to showits phylogenetic tree. H. major was also classified into different clades with H. ovalis due to various factors. The results showed that genetics, tourism, and restoration were topics with the potential to be explored in the future. This study recommended collaborating in multi-institution to transfer knowledge, technologies, and project arrangements for seagrass exploration. Keywords: